Child’s Rights in Sweden: An Experience - Pandey, Saroj (JOURNAL OF INDIAN EDUCATION, 2008)
The rights of the child is one of the major area of concern and since the implementation of the UN Convention on the Rights of the Child 1989 international community has committed itself to the protection of these rights. SIDA and Children’s Ombudsman, Sweden are working in cooperation with each other to organise training programmes for different regions of the world to expose functionaries of these countries about the rights of children and their protection. This article is based on my experiences of a recent visit to Sweden to attend one such training programme on Child’s Rights.